2010
DOI: 10.1080/14772001003748709
|View full text |Cite
|
Sign up to set email alerts
|

Loss of planktotrophy and speciation: geographical fragmentation in the deep-water gastropod genusBathytoma(Gastropoda, Conoidea) in the western Pacific

Abstract: Dispersal capabilities are crucial in how speciation patterns are determined in marine invertebrates. Species possessing a long-living planktonic larva apparently have a dispersal advantage over those with non-planktotrophic development, and their distant populations may exchange genetic material, maintaining a broad geographical range for the species. Recent species of the gastropod genus Bathytoma (Conoidea) are all characterized by non-planktotrophic development, having most probably lost a free-swimming la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…The p-distances calculated for the 16S sequences vary from 0 to 0.027 for within-morphospecies comparisons (mean = 0.012, SD = 0.0072) and from 0.069 to 0.104 for comparisons between morphospecies (mean = 0.082, SD = 0.0109). As the between-group genetic distances (especially for the COI gene) are greater than genetic distances between closely related species of conoideans found in our earlier studies (e.g., Puillandre et al 2009Puillandre et al , 2010Fedosov & Puillandre 2012), the genetic differences found within the H. ocellata species complex support the species hypotheses based on the identified morphospecies.…”
Section: Species Delimitation and Phylogenetic Analysissupporting
confidence: 68%
See 1 more Smart Citation
“…The p-distances calculated for the 16S sequences vary from 0 to 0.027 for within-morphospecies comparisons (mean = 0.012, SD = 0.0072) and from 0.069 to 0.104 for comparisons between morphospecies (mean = 0.082, SD = 0.0109). As the between-group genetic distances (especially for the COI gene) are greater than genetic distances between closely related species of conoideans found in our earlier studies (e.g., Puillandre et al 2009Puillandre et al , 2010Fedosov & Puillandre 2012), the genetic differences found within the H. ocellata species complex support the species hypotheses based on the identified morphospecies.…”
Section: Species Delimitation and Phylogenetic Analysissupporting
confidence: 68%
“…Moreover, the material shows notable differences in size and number of whorls of the protoconch. The latter character is known to vary notably among closely related conoidean species (Bouchet 1990;Puillandre et al 2010), and particularly in the family Raphitomidae (Fedosov & Puillandre 2012;Fedosov & Stahlschmidt 2014). Thus, the species treated in the present study are not cryptic.…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, it has been demonstrated for some conoidean taxa that the switch from planctotrophic to non-planctotrophic development can give rise to adaptive radiation, especially in polar or insular regions, or in groups with narrow bathymetric distribution (Bouchet, 1990;Leal & Bouchet, 1991). Loss of planctotrophy for example, preceded radiation in the polar genus Oenopota (Bogdanov, 1989) or bathyal Indo-Pacific genus Bathytoma (Puillandre et al, 2010).…”
Section: On the Biology And Developmental Plasticity Of Raphitomidaementioning
confidence: 97%
“…It proved useful in solving various taxonomic problems, both at the species and phylogenetic levels (Duda & Kohn, 2005;Cunha et al, 2008;Kantor et al, 2008;Puillandre et al, 2010), and for hypotheses on aspects of the biology, ecology and evolution of the group (Williams & Duda, 2008;Duda & Lee, 2009;Castelin et al, 2012). Many groups of turrids, however, remain unstudied at the molecular level, among which Raphitomidae is of particular importance.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, it has been demonstrated that the switch in some conoidean taxa from the planktotrophic to the non-planktotrophic development has increased their adaptive radiation, especially in polar or insular region, or in groups with narrow bathymetric distribution [3,7]. In the case of Oenopota elongata Bogdanov, 1989, and in the polar genus or bathyal IndoPacific genus Bathytoma Harris & Burrows, 1891, the loss of planktotrophy actually preceded adaptive radiation [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%